2018
DOI: 10.3389/fmicb.2018.00989
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Paraburkholderia terrae Strains to Two Soil Fungi and the Potential Role of Oxalate

Abstract: Fungal-associated Paraburkholderia terrae strains in soil have been extensively studied, but their sensing strategies to locate fungi in soil have remained largely elusive. In this study, we investigated the behavior of five mycosphere-isolated P. terrae strains [including the type-3 secretion system negative mutant BS001-ΔsctD and the type strain DSM 17804T] with respect to their fungal-sensing strategies. The putative role of oxalic acid as a signaling molecule in the chemotaxis toward soil fungi, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Mesorhizobium and Paraburkholderia are also common diazotrophic components of the rhizosphere but have been detected as free-living organisms ( Ahmad et al, 2008 ), and they showed high presence of both these genes. Paraburkholderia was found to have chemotactic sensitivity for oxalate even if it was not directly shown that it can produce it ( Haq et al, 2018 ). Micromonospora also had high oxalate-related gene abundance especially in the first stages of the SW dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Mesorhizobium and Paraburkholderia are also common diazotrophic components of the rhizosphere but have been detected as free-living organisms ( Ahmad et al, 2008 ), and they showed high presence of both these genes. Paraburkholderia was found to have chemotactic sensitivity for oxalate even if it was not directly shown that it can produce it ( Haq et al, 2018 ). Micromonospora also had high oxalate-related gene abundance especially in the first stages of the SW dataset.…”
Section: Discussionmentioning
confidence: 99%
“…led to a significant increase in the population of indigenous collimonads, however no reduction in the fungal biomass was reported. In addition to this, in the same experiment, no increase in the population of common fungal hyphae-associated bacteria such as Pseudomonas and Burkholderia, which are known to feed on fungal metabolites, was detected [ 38 , 53 , 99 , 100 ]. This observation further supports the “hyphal feeding” strategy of collimonads.…”
Section: Discussionmentioning
confidence: 82%
“…First, the active hyphae of fungi in soil often supply (release) small carbonaceous compounds that support the growth of associated bacteria. Thus, compounds such as: maltose, trehalose, L-rhamnose, D-sorbitol, D-glucuronic acid, p-hydroxy-phenylacetic acid, succinamic acid, glucuronamide, L-alanin amine, L-ornithine, glycerol, mannitol, oxalic acid, acetic acid, formic acid, citric acid, fumaric acid and CO 2 have all been shown to be released at fungal surfaces (Frey-Klett et al 2011;Churchland and Grayston 2014;Haq et al 2018). Moreover, hyphae of particular fungi are known to produce inhibitory (i.e.…”
Section: Characteristics Of the Mycosphere And Mycorrhizosphere As Sementioning
confidence: 99%
“…Their network structures enable them to move around substances (e.g. bound carbon) and so carbon sources that are required for growth can be furnished to local bacteria (Haq et al 2018). Moreover, the hyphal networks can also translocate bacterial cells through soil Berthold et al 2016).…”
Section: Introductionmentioning
confidence: 99%